2016
DOI: 10.1007/s00066-016-1029-1
|View full text |Cite
|
Sign up to set email alerts
|

Single dose IOERT versus whole breast irradiation

Abstract: For patients treated with IOERT we noted less asymmetry and high rates of "good or excellent" subjectively derived cosmetic scores. The level of agreement between the subjectively and the objectively derived cosmetic scores was limited. Due to the small sample size and the design of the study no definitive conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Excellent or good cosmesis was scored by patients in 77% and by physicians in 84%. The Netherlands group compared institutional data for women treated with IOERT ( n = 26) or conventional WBRT ( n = 45) based on seven asymmetry features ( 24 ). Features favoring IOERT with smaller differences between treated and untreated breast included breast contour, relative breast area, and breast overlap.…”
Section: Io(e)rt As Sole Partial Breast Radiationmentioning
confidence: 99%
“…Excellent or good cosmesis was scored by patients in 77% and by physicians in 84%. The Netherlands group compared institutional data for women treated with IOERT ( n = 26) or conventional WBRT ( n = 45) based on seven asymmetry features ( 24 ). Features favoring IOERT with smaller differences between treated and untreated breast included breast contour, relative breast area, and breast overlap.…”
Section: Io(e)rt As Sole Partial Breast Radiationmentioning
confidence: 99%
“…After eliminating duplicates, 1659 articles remained but 1575 did not meet the selection criteria; 66/84 remaining papers were excluded for not meeting clinical and outcome criteria. Consequently, only 18 articles that were published in the period 2010–2023 were suitable for inclusion in this meta-analysis and systematic review [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 6 , 8 , 13 , 14 , 20 , 21 , 23 , 24 , 26 , 27 ] reported lowest and highest ages (median lowest age 50 years, range 33–59; median highest age 82.5 years, range 62–91). Five studies [ 14 , 20 , 22 , 25 , 26 ] reported mean ages (65.1 years, range 56.4–69.3).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies concerned breast cancer and 12 studies concerned prostate cancer 22 33 . Among the 7 APBI 34 40 studies, 6 were designed as non-inferiority trials and one did not specify the design of the trial. In the 13 HWBI 41 53 , 2 were designed as non-inferiority trials, 2 as superiority trials andin 9 studies did mention the design of the trial.…”
Section: Resultsmentioning
confidence: 99%